Ichthyofaunistic composition of Veadinho Brook, tributary of Lower Rio Grande River microbasin, Minas Gerais State, Brazil - Gaia da Silva, Ronielson; Camargo, Paulo Ricardo da Silva; Quirino, Micaela de Oliveira; Souza, Fagner de (Revista Brasileira de Ciência, Tecnologia e Inovação, 2023)
Anthropic actions can have negative effects on aquatic communities, such as changes in both the environment and in the composition of local communities. The aim of the current study is to investigate the ichthyofaunistic composition in a lower Rio Grande River tributary. Four regions distributed between two waterfalls were sampled. To do so, 50-minute samplings were carried out at each point, based on using 1.0 x 0.50-m sieves with 3-mm adjacent nodes. Subsequently, diversity indices (richness, abundance, dominance, Shannon-Winner, Simpson and Equitability parameters) were calculated in PAST® software for data analysis purposes. Shapiro-Wilker test was used to analyze data normality, whereas ANOVA test was adopted to analyze significant differences. In total, 1.926 individuals distributed among four orders, four families and six species were sampled. Cyprinodontiformes (49.01%) was the most abundant fish order; it was followed by Characiformes (48.75%), Cichliformes (1.30%) and Siluriformes (0.93%). Interpretive analyses did not indicate significant differences in this parameter, likely due to environmental homogeneity in the sampled regions. Thus, the herein investigated ichthyoaunistic composition may be linked to fish’s adaptive plasticity.